Mental health risk factors for criminal recidivism and mortality in individuals given community sentences - Yukhnenko, D (2021)
Individuals with psychiatric disorders are overrepresented in correctional populations. Given their high prevalence, understanding the role that psychiatric disorders play in criminal behaviour is essential for achieving the primary goal of correctional systems - preventing future crime. Understanding psychiatric disorders is also relevant for mitigating potential health risks, mortality being the most serious, associated with criminal behaviour and sentencing. Despite the apparent need, very few studies have examined the association of psychiatric disorders with criminal recidivism and mortality in non-custodial populations, i.e., individuals given community sentences. The present thesis addresses this research gap and provides recommendations for evidence-based risk management of individuals with psychiatric disorders undergoing community supervision.